EFFECTIVITY TEST OF THE COMBINATION OF ETHANOL EXTRACT MAHKOTA DEWA FRUIT (Phaleria macrocarpa (Scheff.) Boerl.) WITH METFORMIN TO LOWERING BLOOD GLUCOSE LEVELS IN ALLOXAN-INDUCED WISTAR WHITE RATS STRAIN - Katarina Lulu Widyanti; Tanti Azizah Sujono (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Metformin is a first-line biguanid drug for type 2 of diabetes mellitus. Metformin potentially causes liver fibrosis in long-term use, its decrease it in their effectiveness of antidiabetic. Combining metformin with antidiabetic a-glucosidase enzyme inhibitors can increase the effectiveness of metformin. Mahkota dewa fruit is a natural ingredient that has antidiabetic activity with the mechanism of action of inhibiting a-glucosidase enzyme. This study aims to determine the effect of the combination of mahkota dewa fruit extract (EEMF) with metformin on the effectiveness of reducing blood glucose levels in diabetic rats. A total of 20 rats were grouped into 4, namely, group I: given distilled water (negative control); group II: given metformin 45 mg/kgBW; group III: given EEMF 50 mg/kgBW; group IV: given a combination of metformin 45 mg/kgBW and EEMF 50 mg/kgBW. The study was conducted by determining blood glucose levels using the GOD-PAP method. The results showed that the combination of EEMF with metformin had an average decrease per day from after induction to day 7 of 42,9 mg/dL and from day 7 to day 14 of 0,45 mg/dL. It can be concluded that the combination of EEMF dose 50 mg/kgBW with metformin 45 mg/kgBW is not recommended to be used together, because the large decrease has the risk of hypoglycemia effect. Keywords: antidiabetic, alloxan, metformin, fruit of mahkota dewa.